An Assessment of Water Quality in Ramsar Convention Listed Neureni Lake in Pokhara, Nepal - Poudel, Raju Kumar (Prithvi Academic Journal, 2022)
Water is one of the essential substances for the survival of the flora and fauna on the earth. Different physical activities such as photosynthesis, nutrient absorption, respiration and other metabolism processes depend on the quantity of water. This investigation has been carried out to assess the quality of water of Neureni Lake. This lake is listed in Ramsar Convention 2016 (i.e. conservation and sustainable use of wetlands of Nepal). Different physical (transparency, temperature and depth) and chemical parameters such as hydrogen ion concentration (pH), free carbon dioxide (F-CO2), dissolved oxygen (DO), total hardness (TH), total dissolved solids (TDS), total solids (TS), chloride ions (Cl-), magnesium (Mg) and calcium (Ca) were analyzed following the systematic methods recommended by American Public Health Association (APHA, 1999). The results obtained from this analysis have been compared with the standard values of the World Health Organization (WHO) and various lakes. The study shows that all the physico-chemical parameters of Neureni Lake meet the criteria of the WHO of water quality so that the quality of water of Neureni Lake is not so much contaminated with harmful or poisonous substances. In connection to maintaining the water quality of the lake, the physical and chemical components of water should be checked from time to time by controlling domestic sewage, not using pesticides and fertilizers in the field around the lake and controlling the rocky soil coming in the rainy season by making siltation dam.